2008
DOI: 10.1088/1748-9326/3/1/015005
|View full text |Cite
|
Sign up to set email alerts
|

How to improve the estimation of power curves for wind turbines

Abstract: We introduce a dynamical approach for the determination of power curves for wind turbines and compare it with two common methods-among them the standard procedure due to IEC 61400-12-1, i.e. the international standard prepared and published by the International Electrotechnical Commission. The main idea of the new method is to separate the dynamics of a wind turbine's power output into a deterministic and a stochastic part, corresponding to the actual behaviour of the wind turbine and external influences such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 11 publications
4
82
0
Order By: Relevance
“…Gottschall and Peinke (2008) emphasized the impact of short-time dynamics for a proper description of the power conversion process of a wind turbine. Simple sample statistics are not sufficient to capture the characteristics of this process.…”
Section: Scatter Due To Turbulencementioning
confidence: 99%
“…Gottschall and Peinke (2008) emphasized the impact of short-time dynamics for a proper description of the power conversion process of a wind turbine. Simple sample statistics are not sufficient to capture the characteristics of this process.…”
Section: Scatter Due To Turbulencementioning
confidence: 99%
“…Previous work on power performance highlights the role of turbulence intensity (TI) and wind shear in influencing power production (Elliot and Cadogan, 1990;Hunter et al, 2001;Kaiser et al, 2003;Sumner and Masson, 2006;Gottschall and Peinke, 2008;Antoniou et al, 2009;Rareshide et al, 2009;Wharton and Lundquist, 2012a, b;Clifton et al, 2013a;Dörenkämper et al, 2014). Wharton and Lundquist (2012b) also found that vertical TI and turbulence kinetic energy (TKE) affect power performance and Rareshide et al (2009) found that veer affects power performance.…”
Section: Introductionmentioning
confidence: 99%
“…Turbulence affects the wind turbines mainly in two ways: first, the fluctuations that are caused in the extracted wind power (Kaiser et al, 2007;Gottschall and Peinke, 2008), and second, the fluctuations in the loads on different components of a wind turbine . These fluctuations result in inefficient harnessing of wind energy and have the potential to inflict fatigue damage.…”
Section: Introductionmentioning
confidence: 99%